Prediction of Performance in a Short Trail Running Race: The Role of Body Composition. - Alvero-Cruz, José Ramón; Parent-Mathias, Verónica; García-Romero, Jerónimo; Carrillo-de-Albornoz, Margarita; Benítez-Porres, Javier; Ordóñez, Francisco Javier; Rosemann, Thomas; Nikolaidis, Pantelis T.; Knechtle, Beat (Frontiers Media SA, 2019)
The aim of the present study was to examine the role of the classical physiological model of endurance running performance – maximal oxygen uptake (VO2max), %VO2max at ventilatory thresholds (VT), work economy, lactate levels, and body composition on the prediction of short trail running performance. Eleven male trail runners (age 36.1 ± 6.5 years, sport experience 6.6 ± 3.8 years, and mean ± standard deviation) were examined for fat mass and skeletal muscle mass, and performed a graded exercise test to measure VO2max, vVO2max, and VT. Also, they participated in a short 27 km trail run with a positive elevation of +1750 m. Age, years of training and skeletal muscle mass did not correlate with race time (P > 0.05), and fat mass and body mass index (BMI) showed significant correlations with race time (P < 0.05). Heart rate, velocity and VT1 and VT2 were not associated with race time (P > 0.05). Only vVO2max (P = 0.005) and VO2max (P = 0.007) is correlated to race time. Multiple regression models for VO2max accounted for 57% of the total variance. The vVO2max model variable accounted for 60% and the fat mass model for 59.5%. Finally, the combined VO2max and fat mass model explained 83.9% of the total variance (P < 0.05 in all models). The equation for this model is “race time (min) = 203.9956−1.9001 × VO2max + 10.2816 × Fat mass%” (R2 = 0.839, SEE = 11.1 min, and P = 0.0007). The classical variable VO2max together with fat mass percent are two strong predictors for short trail running performance. © Copyright © 2019 Alvero-Cruz, Parent Mathias, Garcia Romero, Carrillo de Albornoz-Gil, Benítez-Porres, Ordoñez, Rosemann, Nikolaidis and Knechtle.
Keywords: Carreras (Atletismo); Ejercicio físico - Aspectos fisiológicos; Fat mass; Maximal oxygen uptake; Performance prediction; Short trail running; Skeletal muscle mass